Could Children’s Gender Predict Their Parents’ Housework Behavior? - Xiaodong Sun; Kaisheng Lai; Hong Han; Chenyan Yang (SAGE Open, 2023)
This study’s objective was to examine whether parents show different patterns in housework behavior in relation to children’s gender. Previous studies have suggested that children’s gender might shape family processes through various paths. However, in married couples, housework behavior is mainly explained by the economic or structural differences between partners, but little is known about the potential relevance between children’s gender and parents’ housework behavior. Using nationally representative data from the Chinese General Social Survey, we examined the link between children’s gender and parents’ weekly housework hours. Two dichotomous indicators represented children’s gender: having at least one son (or not) and having at least one daughter (or not). An ordinary least squares regression model was employed for the analysis. The results indicated that parents who have at least one son, rather than those who have at least one daughter, showed significant differences in housework behavior, with mothers spend more time on housework whereas fathers spend less. The findings suggest that parents do behave differently in relation to children’s gender. By emphasizing its symbolic attribute, we argue that children’s gender constitutes part of the social gender structure related to family processes.